Penyuluhan Nutrisi dan Pemeriksaan Status Gizi Pada Ibu Hamil di Puskesmas Mangarabombang Kabupaten Takalar - Dewi Dewi; Sumarmi Sumarmi; Riska Nuryana; Anita Kartini (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Pregnancy is the intrauterine growth and development of the fetus starting from conception and ending until the start of labor. Mothers' low knowledge about balanced nutrition during pregnancy, infants and toddlers causes incorrect feeding and affects nutritional status. This activity aims to increase mothers' knowledge about balanced nutrition for pregnant women, babies and toddlers and increase mothers' motivation. Achieving this goal is carried out through examining the nutritional status of pregnant women and providing nutritional education using lecture and question and answer methods. The implementation of this activity is planned in 3 stages, namely: preparation stage, implementation and evaluation stage. After counseling and inspection activities, monitoring or evaluation is carried out. After this service activity is carried out, it is hoped that mothers will have strong motivation to fulfill nutritional requirements for toddlers and improve mothers' attitudes and actions in providing balanced nutrition to toddlers. This activity can make a positive contribution in reducing nutritional problems in the Mangarobombang Community Health Center Working Area, Takalar Regency. After this service activity is carried out, it is hoped that mothers will have strong motivation to fulfill the nutrition of pregnant women and improve their attitudes and actions in consuming healthy and nutritionally balanced food. This activity can make a positive contribution in reducing nutritional problems.